Comparison of Flow Cytometric Methods for the Enumeration of Residual Leucocytes in Leucoreduced Blood Products: A Multicenter Study. Issue 4 (18th January 2018) - Zeng, Yang; Dabay, Michelle; George, Virginia; Seetharaman, Shalini; de Arruda Indig, Monika; Graminske, Sharon; Kimpel, Nicole; Schmidt, Anna; Boerner, Amanda; Paradiso, Sarai; Delman, Tatyana; Li, Yunyao; et al.
Abstract: The BD FACSVia™ System features novel designs in hardware, software, and instrument QC. We compared the performance of the BD FACSVia System using the BD Leucocount™ kit with the BD FACSCalibur™ flow cytometer. Leucoreduced platelet (PLT, n  = 252) and red blood cell (RBC, n  = 278) specimens were enrolled at four sites. Each specimen was stained in four tubes using the BD Leucocount kit reagents and acquired on the two systems. BD Leucocount Control cells (high and low) were used to evaluate the inter‐site reproducibility on the BD FACSVia System at three sites over 20 days. Deming regression and Bland–Altman analysis were performed to determine the WBC absolute counts on the BD FACSVia System vs. the BD FACSCalibur system. Assay accuracy for the range of 0–350 WBCs/µl was adequate. For samples with <25 WBCs/µl, the bias with 95% limits of agreement was 0.136 (–1.897 to 2.169) WBC/µl for PLTs ( n  = 184) and 0.170 (–2.025 to 2.365) WBC/µl for RBCs ( n  = 193). For inter‐site reproducibility, the CV% was 6.46% (upper 95% CI 7.16%) for the PLT high control and 9.49% (10.52%) for the PLT low control. The CV% was 7.51% (8.32%) for the RBC high control and 10.76% (11.92%) for the RBC low control. The BD FACSVia System reported equivalent results of WBC absolute counts for leucoreduced PLT and RBC samples compared to the BD FACSCalibur system. The inter‐laboratory reproducibility of the BD FACSVia System met study specifications. © 2018 The Authors. Cytometry Part A Published by Wiley Periodicals, Inc. on behalf of ISAC.